O ensino de jogos e brincadeiras nas aulas de educação física no ensino médio - Ferreira, Geovani Pundrich (2024)
In 2018, the Ministry of Education approved the National Common Curricular Base, a guiding document for basic education, which defines competencies, skills, and learning objectives for better student development in Brazilian schools. One of the main educational modifications is the didactic organization of Physical Education content, so that Brazilian states can plan their actions, having a common point and adapting part of the content to local reality. Considering the low participation of high school students in Physical Education classes, we developed a didactic sequence focused on the content of Games and Play, as we noticed that this cultural educational element is mainly developed in Early Childhood Education and the early years of Elementary School, but is neglected in the later years of Elementary School and in high school. The choice of this content was made because we observed that most students participate more actively in classes when they revolve around this theme. Therefore, our objective is to analyze how a teaching proposal involving Games and Play can contribute to the participation and learning of high school students in Physical Education classes. The theoretical framework briefly addressed the history of Physical Education and its role in high school, the role of Games and Play in student formation, and the characterization of high school youths. The research is considered a pedagogical intervention type, using a qualitative approach, with a state school located in Barra do Garças/MT as the setting and 37 students from a 2nd-year high school class as subjects. For data collection, we used two open questionnaires, one at the beginning and one at the end, a field diary where we recorded interventions and notes regarding class events using observation techniques. We also used an intervention plan in the form of a didactic sequence. The collected data were analyzed following a coding proposal into categories for a comprehensive analysis. A discussion of the results was conducted based on the construction of a didactic sequence with 14 classes, divided into 7 sessions of 2 hours each. We found that students felt motivated to participate in classes beyond mere knowledge acquisition, providing an opportunity for the exchange of other types of knowledge during classes, fostering a more democratic and inclusive teaching approach. It became evident that participation and engagement increased as the classes progressed and with the inclusion of new Games and Play activities. We noticed that previously demotivated and excluded students felt integrated and actively participated after the intervention. Among the challenges, considering the context of Brazilian education and its structural and formative conditions, we highlight the need for more materials, especially in public schools, and the teachers' insecurity in planning an intervention where students are directly responsible for sharing knowledge with their peers. In conclusion, we found that this teaching proposal proves to be a valid alternative in the school environment, as it encourages student engagement in high school Physical Education classes.